Rethinking modernity postcolonialism and the sociological imagination - Bhambra, Gurminder K. (Switzerland Palgrave macmillian, 2023)
Arguing for the idea of connected histories, Bhambra presents a fundamental reconstruction of the idea of modernity in contemporary sociology. She criticizes the abstraction of European modernity from its colonial context and the way non-Western "others" are disregarded. It aims to establish a dialogue in which "others" can speak and be heard.
Keywords: Nation; Politics; Social Theory